Corrosion - Singh, Ambrish (IntechOpen, 2020)
Corrosion is a global threat and a burning topic for new and innovative research. Corrosion causes shut downs, economic losses, delays, failures, accidents, losses of life, and losses in productivity. "Wherever metal is, there corrosion will occur" - this is a general concept as not many protection methods are available to mitigate corrosion. The available methods can only delay the process but cannot stop or protect the metal completely. So there is always a need for good research and inventions in this field. This book includes the recent research work done in the field of corrosion. The chapters are written by reputed authors in the field of corrosion and have been reviewed extensively before acceptance. The chapters focus on different aspects of corrosion to provide readers with a good idea of the overall process. The diversification of the chapters will keep the readers interested and motivated for new innovations in the field of corrosion. It will be very useful to scholars, academicians, researchers, and industrialists.